2005
DOI: 10.1002/clc.4960281004
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between endothelial function in the coronary and brachial arteries

Abstract: SummaryBackground: Endothelial dysfunction is the first step in the progression to atherosclerosis, but little is known regarding whether there is a correlation in endothelial function between the coronary and peripheral arteries.Hypothesis: We investigated the relationship between coronary and peripheral endothelial function.Methods: In 41 patients (mean age 63 years; 23 men, 18 women) with angiographically normal coronary arteries, changes in brachial artery diameter in response to hyperemic flow and subling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
69
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 34 publications
2
69
0
1
Order By: Relevance
“…8 Both measures are modestly correlated with coronary endothelial function, 9,10 and prospective data have remained controversial.…”
mentioning
confidence: 99%
“…8 Both measures are modestly correlated with coronary endothelial function, 9,10 and prospective data have remained controversial.…”
mentioning
confidence: 99%
“…According to previous studies, we found that vascular endothelial functions were impaired in patients with CSF 7,8,13 . Endothelial dysfunction appears to be a generalized process and can be detected in coronary and peripheral arteries before the development of atherosclerosis 14 .…”
Section: Discussionmentioning
confidence: 67%
“…This stimulus makes the endothelium release nitric oxide (NO) with subsequent vasodilatation that can be imaged and quantitated as an index of vasomotor function 6 . Brachial endothelial function has also been found to be associated with CSF 7,8 . Nebivolol is a third-generation highly cardioselective β1-adrenoceptor antagonist and it also affects the L-arginine/ NO pathway, causing vasodilatation by increasing endothelial NO release 9 .…”
mentioning
confidence: 99%
“…Relationships between coronary and brachial artery endothelial function have been demonstrated using ACh and FMD techniques, respectively in individuals with (Anderson et al 1995) and without CAD (Teragawa et al 2005). While there is merit in demonstrating the magnitude of endothelial responses is comparable between arteries, ACh and flow-mediated stimuli activate the endothelium via differing mechanisms.…”
Section: Technical Aspects Of the Fmd Techniquementioning
confidence: 99%